Reaching Parents Through an Online Community. Issue 1 (January 2019) - Boat, Anne; Monteleone, Matthew; Lee, Jennifer J.; Sun, Lena S.
Abstract : Scientific studies in animal models have demonstrated the neurotoxic effects of anesthetic and sedative drugs on the developing brain. Human studies, however, have been limited and less conclusive. The implications for clinical care remain unclear, and there is a critical need for further research on anesthetic toxicity to ensure safe anesthesia practices for infants and children. The sixth PANDA Symposium organized a session on "Engaging Stakeholders to Support Research" to facilitate dialog around improving communication and collaboration among stakeholders and to promote coordinated research efforts. Key stakeholders include patients, families, clinicians, researchers, community organizations, and federal agencies. This article provides an overview of an online platform called the Family Talkboard, a novel method which is destined to enhance patient outreach, engagement, and quality improvement, as well as outcomes research.